Low-carbon cows: From microbial metabolism to the symbiotic planet - Folkers, Andreas; Opitz, Sven; Justus Liebig University Giessen (My University, 2022)
This article focuses on two projects – one at a large chemical company and the other at a small start-up – to intervene in the relations between cows and ruminal microbes to reduce bovine methane emissions. It describes these interventions as ‘symbiotic engineering’: a biopolitical technique targeting holobionts and becoming effective by working on interlaced sets of living things. Based on the analysis of these cases, the article elucidates a planetary symbiopolitics (Helmreich) that connects ‘molecular biopolitics’ (Rose) and ‘microbiopolitics’ (Paxson) to ‘bovine biopolitics’ (Lorimer, Driessen) and the politics of climate change. We critically investigate the spatial imaginaries of symbiotic engineering practices that single out the microbial realm as an Archimedean point to address planetary problems. This technoscientific vision resonates with the notion of the ‘symbiotic planet’ advanced by Lynn Margulis that depicts the Earth System, or Gaia, as a vast set of relations among living things down to the tiniest microbes. Margulis’ concept, as well as the ‘symbiotic view of life’ (Gilbert, Scott, Sapp) has been embraced in recent debates in STS as a way to think of multispecies worldings. The article contributes critically to these debates by showing what happens when the topology of the symbiotic Earth becomes the operating space for symbiotic engineering practices.
Keywords: symbiosis; Lynn Margulis; biopolitics; methane; microbes; climate change; ddc:300